New Technologies as an answer to the museum de-contextualization problem - Προκοπίου, Σαράντης (Πανεπιστήμιο Πελοποννήσου, 2023)
In the context of archaeological museums and outdoor sites, this thesis investigates how Geographic Information Systems (GIS) and digital technologies might be integrated. It looks into the ways in which these technologies might improve the geolocation, recording, interpretation, and presentation of cultural assets. The goal is to close the gap between conventional museum exhibits and engaging, immersive experiences that encourage people to learn and appreciate archaeological items and locations more thoroughly. The introduction to GIS in the thesis' first section highlights its tools and capacities for geolocation and the recording of cultural heritage. The significance of data organization and verification is emphasized in order to guarantee the accuracy and comprehensiveness of the cultural heritage database. Also examined is the idea of thematic interactive maps and their benefits for informational purposes. The thesis then explores how technology and digital interpretation are combined in museums, concentrating on how augmented reality could improve visitor experiences. It examines ethical issues that arise in the use of new technologies and discusses the difficulties and restrictions involved with their use. Examining decontextualization techniques at museums aims to comprehend the effects of taking things out of their original setting. The thesis emphasizes the significance of preserving context and investigates methods for successfully contextualizing items in a museum setting. The thesis also includes two case studies: the Philippi archaeological site and the Archaeological Museum of Kavala. These case studies show how GIS and augmented reality could be applied practically and assess how they affect the contextualization of artifacts, visitor interpretation, and connections to education. A SWOT analysis is carried out for each case study, and the implementation process's difficulties and restrictions are highlighted. This thesis underlines the value of incorporating GIS and digital technology in outdoor archaeological sites and museums. It offers information on these technologies' prospective applications, advantages, and implementation difficulties. Museums may develop immersive experiences that engage visitors, protect cultural heritage, and advance educational goals by utilizing GIS and digital interpretation.
Keywords: Μουσεία -- Διαδραστικά πολυμέσα; Τεχνικές μουσείων -- Τεχνολογικές καινοτομίες; Μουσειακές εκθέσεις -- Τεχνολογικές καινοτομίες; Μουσεία -- Τεχνολογικές καινοτομίες; Εικονικά μουσεία; Πολιτιστική κληρονομιά -- Τεχνολογικές καινοτομίες; Τεχνολογικές καινοτομίες -- Εκθέσεις; Μουσεία -- Εκπαιδευτικές απόψεις; Μουσεία -- Εκπαιδευτικές απόψεις -- Περιπτωσιολογικές μελέτες; Ιστορικοί χώροι -- Διαδραστικά πολυμέσα; Ιστορικοί χώροι -- Διαδραστικά πολυμέσα -- Περιπτωσιολογικές μελέτες; Αρχαιολογικοί χώροι -- Γεωγραφικά συστήματα πληροφοριών; Αρχαιολογία -- Γεωγραφικά συστήματα πληροφοριών -- Περιπτωσιολογικές μελέτες; Museum; New Technologies; Augmented Reality; Virtual Reality; Kavala; Decontextualization; Cultural Heritage; Interactive Map; Education; Visitors; Μουσείο; Νέες Τεχνολογίες; Επαυξημένη Πραγματικότητα; Εικονική Πραγματικότητα; Καβάλα; Αποπλαισίωση; Πολιτιστική Κληρονομιά; Διαδραστικός Χάρτης; Εκπαίδευση; Επισκέπτες